2021
DOI: 10.1111/jeb.13872
|View full text |Cite
|
Sign up to set email alerts
|

Structural dissimilarity of partners' immune genes increases sperm viability in women's reproductive tract

Abstract: Human leucocyte antigen (HLA) genes appear to mediate pre‐ and post‐copulatory mate choice towards HLA‐dissimilar (‘compatible’) partners. However, since genetically distinct alleles often have similar immunogenic properties, genetic dissimilarity is not necessarily an accurate predictor of the functional compatibility of HLA alleles and, hence, may not reflect partners' true compatibility. Furthermore, it has remained unclear whether other genes of the immune system could also play a role in male–female compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…In both studies, sperm performance was also found to be higher in human leucocyte antigen (HLA) dissimilar male–female combinations, which suggests that the female reproductive tract may non-randomly promote gamete fusion between HLA compatible partners. Magris et al (2021) also demonstrated that in addition to HLA, sperm performance in the female reproductive tract is dependent on the structural similarity of male and female immunoglobulins (antibodies). Together with the earlier findings in different animal species, these results indicate that one of the primary functions of GMMC may be to ‘evaluate’ the immunogenetic compatibility of the reproductive partners prior to gamete fusion.…”
Section: Cryptic Female Choice and Gamete-mediated Mate Choicementioning
confidence: 99%
See 1 more Smart Citation
“…In both studies, sperm performance was also found to be higher in human leucocyte antigen (HLA) dissimilar male–female combinations, which suggests that the female reproductive tract may non-randomly promote gamete fusion between HLA compatible partners. Magris et al (2021) also demonstrated that in addition to HLA, sperm performance in the female reproductive tract is dependent on the structural similarity of male and female immunoglobulins (antibodies). Together with the earlier findings in different animal species, these results indicate that one of the primary functions of GMMC may be to ‘evaluate’ the immunogenetic compatibility of the reproductive partners prior to gamete fusion.…”
Section: Cryptic Female Choice and Gamete-mediated Mate Choicementioning
confidence: 99%
“…Consequently, these female-derived secretions could potentially enable diagnosis of the reproductive incompatibility of the partners without the need to fertilise the oocytes (cf. Jokiniemi et al , 2020a , b ; Magris et al , 2021 ). Furthermore, female reproductive secretions could also open novel possibilities for the development of biologically more realistic functional tests for sperm fertilisation capability and male fertility.…”
Section: Clinical Significance and Future Challengesmentioning
confidence: 99%
“…However, diagnosing infertility is extremely challenging, and in up to 40% of cases, infertility remains unexplained [ 50 ]. Recent studies have shown that, in addition to pathological conditions, fertilization failure may also frequently result from gamete-level incompatibility of the reproductive partners [ 20 , 21 , 22 , 48 , 51 ]. Together these earlier findings indicate that development of clinical tests for incompatibility could have great potential in improving the accuracy of infertility diagnostics and thus facilitating the development of more personalized infertility treatments [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, different male–female combinations often differ in their genetic compatibility, which has been assumed to lead to the evolution of polyandry. In other words, selection mechanisms for postmating incompatibility avoidance are expected to evolve only in polygamous mating systems (but see Jokiniemi, Kuusipalo, et al, 2020 ; Jokiniemi, Magris, et al, 2020 ; Magris et al, 2021 ). However, these traditional models of sexual selection have almost completely ignored the possibility that both sperm competition and cryptic female choice among ‘sibling’ sperm can occur also in monogamous species (but see Ezawa & Innan, 2013 ; Sutter & Immler, 2020 ).…”
Section: Evolutionary Significance Of Within‐male Cfcmentioning
confidence: 99%